The Transient Electromagnetic method (TEM) in geothermal exploration. Processing and 1D inversion of a TEM sounding from Reykjanes, SW-Iceland - Elías Eyþórsson 1991- (2015)
Resistivity methods are among the most powerful geophysical methods in geothermal exploration. This is because the resistivity of rocks relates directly to a number of parameters which characterize a geothermal system. Of these, the most important factors are temperature, surface alteration, salinity and porosity. However, if resistivity is to be used as an "indirect thermometer" in such a way, great care is needed as this only holds true when the alteration and the rock temperature are in equilibrium. In the TEM method a large square loop of wire is placed around the target site and a current in generated in the loop. The current is then abruptly terminated which induced currents in the ground. This current decays through Ohmic losses and as it decays it creates yet more current and the current diffuses downwards and outwards. This diffusion of current can be measured at the surface using a receiver coil and as the diffusion of the current is dependent on resistivity structure at depth, the decay (measured as induced voltage in the receiver coil) as a function of time can be used to calculate resistivity as a function of depth.\\ TEM measurement is made near a fumarole in a high temperature area in SW-Iceland and a resistivity model is calculated. The model is typical of a high temperature area, from the surface resistivity is a sharp decrease to a low resistivity zone at about 40 to 300 meters, followed by a steady increase in resistivity from that point.